Restoring drylands, strengthening resilience: Insights from a Climate-Smart Village in Htee Pu, Nyaun Oo, Myanmar - Barbon, Wilson John; Myae, Chan; Su, Myat Noe; Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
The brief talks about the emerging insights from a Climate-Smart Village in Htee Pu, Nyaun Oo, Myanmar. It documents a range of strategies that help farming communities in the central dry zones of the country to cope with lower rainfall and other climate change impacts.